The Impact of Board Diversity on Sustainability Finance: The Mediating Role of Green Intellectual Capital in Indonesian Manufacturing Firms - Kustinah, Siti; Susyani, Novi; Marlina (Fakultas Ekonomi dan Bisnis Islam, 2025)
This research examines the influence of board diversity on sustainability finance with green intellectual capital as a mediating variable. This topic is important because it supports companies' efforts to achieve sustainable development goals (SDGs) through a financial approach that considers environmental and social aspects. The main issue being examined is whether board diversity affects sustainable finance, and whether green intellectual capital can mediate that relationship. This research offers a new contribution by integrating three main concepts board diversity, green intellectual capital, and sustainability finance within the context of manufacturing companies in Indonesia, which have not been simultaneously studied in the previous literature. This research uses a quantitative method with a verification approach. The sample consists of 20 manufacturing companies purposively selected from the IDX for the period 2018–2022. Data analysis was conducted using Partial Least Square (PLS). The results show that board diversity has a significant negative impact on green intellectual capital, but does not have a significant impact on sustainability finance. GIC also does not mediate that relationship. The diversity of the board needs to be managed strategically to avoid conflicts that could hinder the company's sustainable financial performance.